2004
DOI: 10.1016/j.bbrc.2004.10.143
|View full text |Cite
|
Sign up to set email alerts
|

Crp of Streptomyces coelicolor is the third transcription factor of the large CRP-FNR superfamily able to bind cAMP

Abstract: The chromosomal inactivation of the unique transcription factor of Streptomyces coelicolor that displays a cyclic-nucleotide-binding domain, Crp(Sco), led to a germination-defective phenotype similar to the mutant of the adenylate cyclase gene (cya) unable to produce cAMP. By means of cAMP affinity chromatography we demonstrate the specific cAMP-binding ability of Crp(Sco), which definitely demonstrate that a Cya/cAMP/Crp system is used to trigger germination in S. coelicolor. However, electromobility shift as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…In addition, a helix-turn-helix DNA binding motif of the CRP/FNR family was identified in the carboxyterminal region of the TTHA1437 protein ( 162 F to 203 R). S. coelicolor CRP, which is the closest homolog of the TTHA1437 protein among the proteins with known functions, has been indicated to bind cAMP, and the residues that are involved in the cAMP binding have been predicted based on a threedimensional model of the S. coelicolor CRP (12). Based on the amino acid alignment shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a helix-turn-helix DNA binding motif of the CRP/FNR family was identified in the carboxyterminal region of the TTHA1437 protein ( 162 F to 203 R). S. coelicolor CRP, which is the closest homolog of the TTHA1437 protein among the proteins with known functions, has been indicated to bind cAMP, and the residues that are involved in the cAMP binding have been predicted based on a threedimensional model of the S. coelicolor CRP (12). Based on the amino acid alignment shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the amino acid alignment shown in Fig. 1 However, the residues involved in heme binding in CooA (71) are not present in the TTHA1437 protein, as in cases of S. coelicolor CRP and C. glutamicum GlxR, which also belong to the CooA subgroup, but are suggested to be cAMP receptor proteins (12,29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome sequencing and functional studies have demonstrated that the CRP family transcriptional regulators are widely distributed in gram-negative and gram-positive bacteria, where they regulate diverse processes. These pathways include phototaxis and heterocyst formation in cyanobacteria (36), anaerobic respiration in Shewanella oneidensis (41), germination and morphological development in Streptomyces coelicolor (12), Mycobacterium tuberculosis virulence in mice (40), quorum sensing and motility in Vibrio cholerae (29), and phytopathogenicity and cell-cell communication in Xanthomonas campestris (11,19).…”
mentioning
confidence: 99%